True power detector for RF PAb Built-in calibration and testing - José Machado da Silva (2011)
Different built-in self testing schemes for RF circuits have been developed resorting to peak voltage detectors. These are simple to implement but provide a conditional RF power measurement accuracy as impedance is assumed to be known. A true power detector is presented which allows obtaining more accurate measurements, namely as far as output load variations are concerned. The theoretical fundaments underlining the power detector operating principle are presented and simulation and experimental results obtained with a prototype chip are described which confirm the benefits of measuring true power, comparing to output peak voltage, when observing output load matching deviations and complex waveforms.